2017
DOI: 10.1177/2050640616646528
|View full text |Cite
|
Sign up to set email alerts
|

Controlled attenuation parameter using the FibroScan® XL probe for quantification of hepatic steatosis for non‐alcoholic fatty liver disease in an Asian population

Abstract: Background: The FibroScan Õ XL probe reduces failure of liver stiffness measurement (LSM) and unreliable results in obese patients. Objective: The objective of this article is to evaluate the accuracy of controlled attenuation parameter (CAP) obtained using the XL probe for the estimation of hepatic steatosis in patients with non-alcoholic fatty liver disease (NAFLD). Methods: Adult NAFLD patients with a liver biopsy within six months were included and were examined with the FibroScan Õ M and XL probes. Histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 36 publications
2
51
1
1
Order By: Relevance
“…9 In a separate study using histology as the reference standard, we found CAP obtained using the XL probe to have similar accuracy as the M probe for the estimation of hepatic steatosis in NAFLD patients. 10 In that study, we observed that CAP obtained using the XL probe tended to be higher compared with the M probe in the overall population as well as for the different grades of hepatic steatosis. Recently, an individual patient data meta-analysis composing of 2735 patients provided optimal cut-offs for CAP obtained using the M probe for the diagnosis of the different grades of hepatic steatosis.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…9 In a separate study using histology as the reference standard, we found CAP obtained using the XL probe to have similar accuracy as the M probe for the estimation of hepatic steatosis in NAFLD patients. 10 In that study, we observed that CAP obtained using the XL probe tended to be higher compared with the M probe in the overall population as well as for the different grades of hepatic steatosis. Recently, an individual patient data meta-analysis composing of 2735 patients provided optimal cut-offs for CAP obtained using the M probe for the diagnosis of the different grades of hepatic steatosis.…”
Section: Introductionmentioning
confidence: 75%
“…This is consistent with the observation in our previous study on NAFLD patients. 10 However, the effect appears to be saturated by increasing BMI. This preliminary observation should be corroborated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies including small cohorts have assessed the diagnostic accuracy of CAP using XL probe . The sensitivity analyses reveal that CAP measurements were significantly higher using XL probe compared with M probe in the lower grade of hepatic fat content.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies including small cohorts have assessed the diagnostic accuracy of CAP using XL probe. (34,35,44) The sensitivity analyses reveal that CAP measurements were significantly higher using XL probe compared with M probe in the lower grade of hepatic fat content. Similarly, Chan et al (35) have shown significant higher value of CAP using XL probe compared with M probe in an Asian NAFLD cohort.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation